DAMPAK ACFTA TERHADAP KINERJA PEREKONOMIAN CHINA - Apriliantini, Rezky; Hanafi, Ridzky Hasan; Mahendra, Akmal (FISIP Universitas Tanjungpura, 2023)
This study discusses international trade that occurs in the interaction of ACFTA (ASEAN-China Free Trade Area) which is a free market cooperation established by countries in Southeast Asia and China. This cooperation is based on the concept of Liberalism theory which aims to create a trade area without barriers and in the principle of equality by reducing or eliminating tariffs to fellow member countries. In this study, attempts to show the results of the analysis of the impact of ACFTA on the positive performance of the Chinese economy so as to prove the feasibility of the cooperation that has been carried out can provide benefits for the countries involved. The existence of this cooperation is also an opportunity that China as a great power does not waste to expand its influence in the economic field by targeting the Southeast Asian market and its consumerism, as evidenced by China's trade balance which has experienced a constant increase regardless of its surplus and deficit. This writing uses a type of qualitative research with a descriptive approach with library research data collection techniques sourced from reference books, scientific journals, papers and reliable articles to support the explanation in this paper.